Konsepsi Pengaturan Fosfor Putih Dalam Konflik Bersenjata - Christopher Fallen, Andy; Anwar, Arman; Tuhulele, Popi (Universitas Ekasakti, 2024)
In October 2023, there were several white phosphorus explosions fired by Israeli forces in a military operation over the Gaza city port and two rural locations along the Israel-Lebanon border. Israel-Lebanon border. The use of White Phosphorus as a weapon is in practice very lethal and torturous to both combatants and civilians. However, there is no regulation that implicitly prohibits the use of White Phosphorus in armed conflicts, resulting in the parties to the conflict using White Phosphorus. armed conflict, resulting in the parties warring parties can the use of White Phosphorus freely and resulted in great torment for people exposed to sparks from white phosphorus. This writing uses normative research methods explorative research method, with the problem approach The approaches used are statutory, conceptual, historical, and case approaches. Sources of legal material in this writing are primary legal materials, secondary, and tertiary legal materials. Technique technique of collecting legal materials using literature studies which are then analyzed qualitatively. qualitatively. From this research, it is concluded that based on the analysis Geneva Gas Protocol Conventional 1925, Chemical Weapons Convention of 1992, Protocol III of Convention on Certain Conventional Weapons 1980, the initial design of white phosphorus is not included in the categorization of white phosphorus. of white phosphorus is not included in the categorization of weapons in the three legal arrangements above. in the three legal arrangements above. However, based on reports related to the use of white phosphorus, two dangerous properties were found, namely, it contains toxic chemicals and causing burns. Based on the effects caused white phosphorus is ideally categorized as an incendiary weapon, supported by the opinion of the International Committee of Red Cross.